The use of innovative means and methods of rehabilitation intervention for upper limb injuries in military personnel (literature review) - Semeniuk, Iryna; Antonova-Rafi , Yuliya (The Ukrainian Scientific Medical Youth Journal, 2025)
the article outlines the characteristics of upper limb injuries in military personnel caused by gunshot and shrapnel wounds, fractures, neuropathies, and soft tissue injuries. Special attention is given to innovative rehabilitation approaches that promote the recovery of mobility, coordination, and limb functionality. The effectiveness of modern developments and methodologies in robotics and virtual reality for upper limb rehabilitation, as presented in scientific literature from 2021 to 2024, is analyzed concerning various types of injuries and recovery periods. These technologies demonstrate high potential in physical therapy by ensuring controlled and repetitive movements to activate muscle memory, stimulating sensorimotor functions, and creating a motivational environment. The necessity for further research is substantiated to confirm their clinical significance and long-term effectiveness. The summarized comparative information will serve as a valuable tool for physical therapists in selecting the most optimal innovative means and methods, as well as in developing more effective individualized rehabilitation programs for military personnel with upper limb injuries.